2008
DOI: 10.1128/jvi.01821-07
|View full text |Cite
|
Sign up to set email alerts
|

Egress of Light Particles among Filopodia on the Surface of Varicella-Zoster Virus-Infected Cells

Abstract: Varicella-zoster virus (VZV) is renowned for its very low titer when grown in cultured cells. There remains no single explanation for the low infectivity. In this study, viral particles on the surfaces of infected cells were examined by several imaging technologies. Few surface particles were detected at 48 h postinfection (hpi), but numerous particles were observed at 72 and 96 hpi. At 72 hpi, 75% of the particles resembled light (L) particles, i.e., envelopes without capsids. By 96 hpi, 85% of all particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…The samples were extracted from the tissue culture dish. Sections made with a diamond knife were stained with uranyl acetate and lead citrate and observed under a JEOL 1230 electron microscope, as described previously (4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were extracted from the tissue culture dish. Sections made with a diamond knife were stained with uranyl acetate and lead citrate and observed under a JEOL 1230 electron microscope, as described previously (4).…”
Section: Methodsmentioning
confidence: 99%
“…A recent paper from Storlie et al (42), reporting a delayed accumulation of the late VZV protein glycoprotein C (gC), suggested that an impairment in the expression of specific viral genes during infection of cultured cells could contribute to such low titers (4). An alternative and not mutually exclusive explanation for the low yields of VZV comes from a separate set of reports, which showed that egressing VZV particles acquire the final envelope at the level of the trans-Golgi network (13) and are then detectable both on the cell surface and within large cytoplasmic vacuoles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of infected and uninfected cells were prepared for confocal microscopy by methods described previously (7). Briefly, the samples were fixed with paraformaldehyde and permeabilized with 0.05% Triton X-100 in phosphate-buffered saline (T-PBS) and then blocked in 5% nonfat milk with 2.5% normal goat serum for 2 h at room temperature (RT).…”
Section: Construction Of Plasmidsmentioning
confidence: 99%
“…Samples were processed for scanning electron microscopy by methods described previously (7). Briefly, following initial fixation with paraformaldehyde and antibody labeling steps, the sample was further fixed with 4% glutaraldehyde in PBS and then stained with 1% OsO 4 in double-distilled water (ddH 2 O), followed by dehydration in a graded series of ethanol-water mixtures from 25% ethanol to 100% ethanol and then 100% hexamethylene disilane (HMDS).…”
Section: Construction Of Plasmidsmentioning
confidence: 99%